A new leafy liverwort of Frullania (Frullaniaceae, Porellales) from the mid‐Cretaceous Kachin amber, Myanmar. (4th August 2021) - Li, Ya; Wang, Yong‐Dong; Feldberg, Kathrin; Wang, Qiang; Yang, Xiao‐Ju
Abstract : With over 300 extant species, the nearly worldwide‐distributed genus Frullania is one of the most species‐rich genera of leafy liverworts and the sole extant genus of Frullaniaceae. Amber fossil record of Frullania is also rather diverse, with inclusions known from several amber deposits. The earliest fossils are F. baerlocheri, F. cretacea, and F. partita from the mid‐Cretaceous Kachin amber, Myanmar. Here, we describe a new fossil species of Frullania as F. kachinensis sp. nov., based on seven sterile gametophyte fragments from three pieces of Kachin amber. This new species is characterized by leaf dorsal lobes mostly with rounded apexes, leaf ventral lobules inserted in approximately 30–90 μm distance to stem, lanceolate styli, and deeply bilobed underleaves with entire‐margined to toothed lobes and V‐shaped sinuses. Morphological comparisons indicate that F . kachinensis shows mosaic character combinations of two coeval species F . cretacea and F . partita . The leaf lobes of F . kachinensis resemble those of F . cretacea, while the underleaves are more similar to those of F . partita . But in taphonomy, F. kachinensis is preserved together with Protofrullania cornigera or F . baerlocheri in the same amber, which could indicate that these three species might live in the same habitat and even on the same tree. The fossils presented in this study provide additional evidence for the presence of a diverse liverwort flora, mostly composed of Frullaniaceae lineages in the mid‐Cretaceous Kachin amber forest. Abstract : Here, we describe some liverwort inclusions within mid‐Cretaceous Kachin amber as Frullania kachinensis sp. nov. (Frullaniaceae). It combines key morphological features of two coeval species Frullania cretacea and Frullania partita, while cluster analysis has F . kachinensis as more similar to F . cretacea .